Social Justice in a Legal Perspective: An Analysis of Inequality in Access to Public Services - Fitri Arianti; Anis Noviya (Ipso Jure, 2026)
Social justice in public services is a fundamental element in a state based on the rule of law, which prioritizes public welfare. Although it is normatively guaranteed in the constitution and various laws and regulations, its implementation still faces various obstacles, particularly related to unequal access to public services. This study aims to analyze the manifestation of social justice from a legal perspective and examine the influence of normative ambiguity in public service regulations on unequal access. The research method used is normative legal research with a legislative and conceptual approach, supported by primary, secondary, and tertiary legal materials, and analyzed qualitatively using deductive reasoning. The results show that normative ambiguity in public service regulations creates legal uncertainty, expands the scope for discretion of officials, and increases the potential for abuse of authority. This condition results in the emergence of service discrimination, unequal service quality between regions, and the marginalization of vulnerable groups. Furthermore, a gap is found between the ideal legal norm (das sollen) and the implemented practice (das sein), indicating that the application of the principle of social justice is not yet optimal. Therefore, normative reconstruction is needed through the formulation of clearer, more operational, and measurable regulations, as well as strengthening monitoring and sanction mechanisms to ensure equal access to public services.